IEEE Antennas and Propagation Society International Symposium. Digest. Held in Conjunction With: USNC/CNC/URSI North American R
DOI: 10.1109/aps.2003.1217482
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable dual-band dipole antenna on silicon using series MEMS switches

Abstract: This paper picsenls a reconfigurable dual-band 4.86 and 8.98 GHa dipole anlenna on silicon using scrics MEMS switches. The effccts of series MEMS switches on the antenna performance are studicd. Thc design is performed using thc 3D electromagnetic simulator HFSS'. Using the dcsigned series MEMS switches, thc obtained antenna m u m loss is -lO.ZdB and -21.6dB, at the lower and uppcr frequencies, respectively. However, comparable to the case of ideal switches, a frequency shiA of0.4% and of 2.8% at the lower and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…However, if frequency shifting is compared with other researches, it shows significant result. As the research conducted by Kiriazi et al [6], showed that the antenna that switched by using RF-MEMS operate in dual frequencies and have shifting frequencies 20 MHz for first frequency and 260 MHz for second frequency. In another research [7], where the antenna switched by using varactor diode, achieve dual frequency shifting 357 and 126 MHz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if frequency shifting is compared with other researches, it shows significant result. As the research conducted by Kiriazi et al [6], showed that the antenna that switched by using RF-MEMS operate in dual frequencies and have shifting frequencies 20 MHz for first frequency and 260 MHz for second frequency. In another research [7], where the antenna switched by using varactor diode, achieve dual frequency shifting 357 and 126 MHz.…”
Section: Resultsmentioning
confidence: 99%
“…However, using silicon as photoconductive switches will require complicated technique during it insertion process on antenna substrate and silicon has high cost. Other techniques, is done previously by Kiriazi et al in [6]. In this work, open and short of RF-MEMS switches were assembled on antenna which has a high-resistivity silicon substrate.…”
Section: Introductionmentioning
confidence: 99%
“…reconfigurable antenna of multi-band and multi-mode can replace multiple antennas based on one vehicle,decreases the developing cost,space and weight of 1 …”
Section: Introductionmentioning
confidence: 99%
“…The reconfigurable antennas contain defferent types:frequency reconfigurable,radiation pattern reconfigurable, frequency and pattern reconfigurable,polarization reconfigurable,and so on. 1,2 In recent years,with development of MEMS technology,especially developing of MEMS switches of high performance and low power cost,reseach on the reconfigurable antennas is deepened, technology concerned with the reconfigurable antennas is studyed by scholars at home and abroad. [3][4][5][6] MEMS switches have much excellent radio frequency performance,such as small size, low conducting insertion loss within broad bandwidth,high disconnecting isolation and low parasitic capacitance.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamically, modifications of antenna radiation characteristics, such as resonance frequency, bandwidth, radiation pattern, and polarization, are the major advantages of reconfigurable antennas over traditionally fixed operating antennas [1,2]. Design methodology of these antennas encounters some challenges.…”
Section: Introductionmentioning
confidence: 99%